LOW CARBOHYDRATE SPECIFICITY OF RAT DUODENUM WALL MUCOSA IN ADMINISTRATION OF CRYOPRESERVED PLACENTA AND ACUTE PERITONITIS - Shepitko, K.V. (World of Medicine and Biology, 2014)
Intubation of duodenum mucosa by complex of lectins has established that the HPA galactose-specific lectin evoked the increased expression from 75% to 100% on the 7-14 days of the study, indicating about the activation of secretion production in cells of crypt-villus system. Fucose-specific marker (PFA) is intended to estimate the quality of mucus-producing in goblet cells of villi and crypts of duodenum wall mucosa, whereas mannose-specific marker (LSA) – in the crypt. Change of expression of receptors to WGA and SNA sialo-specific lectins are markers of recovery of protective functions of enterocytes (with brush border and without a border) of duodenum mucosa. Acceleration by 75% of proliferative processes in the crypt-villus system after administration of cryopreserved placenta on the 14 day of the study has been noted. Restoration of Paneth cells’ reaction to WGA lectin by 75% has been also detected in intact group, too, indicating about normalization of antibacterial protection in crypt.